Anmeldelse af Annika Suominen: The Principle of Mutual Recognition in Cooperation in Criminal Matters. A study of the principle in four framework decisions and in the implementation legislation in the Nordic Member State. - Petter Asp (Nordisk Tidsskrift for Kriminalvidenskab)
Review of Annika Suominen:The Principle of Mutual Recognition in Cooperation in Criminal Matters. A study of the principle in four framework decisions and in the implementation legislation in the Nordic Member State.